Messiaanse vredestichters: Intertekstuele relaties tussen Zacharia 9–14 en het Evangelie van Matteüs - Weren, Wilhelmus Johannes Cornelis (HTS teologiese studies, 2015)
Messianic peacemakers: Intertextual relationships between Zechariah 9-14 and the Gospel of Matthew. This article deals with images of war, violence and peace and with the role of messianic leaders in Deutero-Zechariah and the way in which texts from Zechariah 9–14 have been interpreted in the Gospel of Matthew. The first section describes the lines of meaning in Zechariah 9–14 on the basis of word fields related to violence and universal peace. The second section discusses Deutero-Zechariah’s own position in the development of messianic expectations in Old Testament texts. In the third section, the question is asked how the meaning of texts from Zechariah 9–14 about messianic leaders has been influenced by earlier prophetic texts, and how these texts in their turn have been transformed and updated in the Gospel of Matthew, which contains explicit quotations from Deutero-Zechariah in 21:5; 26:15; 26:31 and 27:9–10. The fourth section summarises some interesting semantic shifts appearing in Matthew’s gospel compared to Deutero-Zechariah. Moreover, some critical comments are presented against the idea defended in some recent studies that there is a sharp tension between Jesus’s role in Matthew as the bringer of a peaceful ethical message, and his violent and vindictive role at the final judgement. At the end of this article, the burning question is raised whether Zechariah’s and Matthew’s messages, both of which are characterised by a certain degree of exclusivity, can play a constructive role in modern multi-religious discussions about common roads leading to global peace.